Internal Control Analysis Of Merchandise Inventory At Gallery Rj Bengkulu - Rafiul, Zurry; Anggriani, Ida; Astuty, Kamelia (Jurnal Fokus Manajemen, 2024)
The aim of the research is to determine the internal control system for merchandise inventory at Gallery RJ Bengkulu based on Mulyadi's theory (2020:488). The analytical method used in this research is a comparative descriptive method.The research results show that there is no compatibility between Mulyadi's theory (2020:488) and the situation that occurred at Gallery RJ Bengkulu for organizational elements, because according to Mulyadi's theory the physical inventory count must be carried out by a special committee formed apart from warehouse employees. Meanwhile, what happened at Gallery RJ Bengkulu was that the physical counting was carried out directly by warehouse employees and display employees. For the elements of the authorization system and recording procedures, there are conformities and discrepancies between Mulyadi's theory (2020:488) and Gallery RJ Bengkulu, the discrepancies are found in the list of physical inventory count results signed by the committee chairman, while in Gallery RJ the inventory calculation is signed by the store manager. Furthermore, the physical inventory count and recording of the results of the physical inventory count are based on physical count cards whose veracity has been verified. There are compatibility and inconsistencies between Mulyadi's theory (2020:488) and Gallery RJ Bengkulu for elements of healthy practice, because in Gallery RJ Bengkulu the physical calculation cards for merchandise inventory are not numbered sequentially because inventory is only recorded in the inventory of goods calculations. Conformity lies in the calculation of inventory of goods having been carried out three times in one month